2009
DOI: 10.1295/polymj.pj2009047
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Polyethylene Oxide Doped with NH4I Salt

Abstract: Dielectric parameters were studied over a frequency range from 10 Hz to 335 kHz at room temperature as a function of frequency and salt concentration. Permittivity (" 0 ) and dielectric loss (" 00 ) data were fitted in the frequency domain using Yan and Rhodes model in order to estimate the relaxation times for PEO electrolytes. Due to the excellent fitting obtained using this model, PEO/NH 4 I electrolytes can be presented in equivalent circuit as RC in parallel circuits connected in series Addition of NH 4 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In the continuity of our ongoing studies 1,15 19 into the MWCNTs with different neat polymers such as polystyrene, polycarbonate, and so on, in the present study, a novel dispersion behavior of MWCNTs was obtained through pretreatment of MWCNTs at different pH values. In our previous work, 1 we functionalized MWCNTs with β-HNA and observed that β-HNA molecules adsorb onto the surface of MWCNTs due to inherent hydrophobic/hydrophilic sites and create electrostatic charge on the surface.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In the continuity of our ongoing studies 1,15 19 into the MWCNTs with different neat polymers such as polystyrene, polycarbonate, and so on, in the present study, a novel dispersion behavior of MWCNTs was obtained through pretreatment of MWCNTs at different pH values. In our previous work, 1 we functionalized MWCNTs with β-HNA and observed that β-HNA molecules adsorb onto the surface of MWCNTs due to inherent hydrophobic/hydrophilic sites and create electrostatic charge on the surface.…”
Section: Introductionmentioning
confidence: 80%
“…Besides, commercial thermoplastic polymer such as polyethylene (PE), polypropylene (PP), poly (vinyl alcohol) ( PVA), polyvinyl chloride (PVC) ….etc are the mostly and widely used plastic in the industrial applications because they are cheap, durable, hard, and easily worked. 1 20 Despite of the extensive studies 1 27 of such materials, multiwalled carbon nanotubes (MWCNTs)-polymer nanocomposites, many important aspects of the electronic and optical properties of these materials are still not fully resolved. Consequently, it will be very interesting to study the effect of pretreatment of MWCNTs using a new method to improve their dispersion in neat polymer to obtain polymer nanocomposites that have attractive properties for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that, at the domain frequency range, the relaxation process is due to viscoelastic relaxation process. 23,26,27 …”
Section: Rheological Propertiesmentioning
confidence: 99%